Cordulegaster sarracenia, n. sp. (Odonata: Cordulegastridae) from east Texas and western Louisiana, with a key to adult Cordulegastridae of the New World - Abbott, John C.; Hibbitts, Troy D. (Zootaxa, 2011)
Cordulegaster sarracenia is described from spring seepages in pitcher plant bogs of southeast Texas and western Louisiana. It is most closely related to C. sayi of the C. diastatops group. It is unique among all North American species of its genus in having the mesepimeral and metepimeral stripes distinctly paler than the mesepisternal stripes in combination with yellow bands on S3–8 that are interrupted middorsally by the carina.